Efficient Catalysis of the Aerobic Baeyer–Villiger Oxidation over a Bifunctional Catalyst Based on Cobalt Tetraphenylporphyrin Intercalated into Zn2Al Hydrotalcite. Issue 1 (25th November 2014) - Zhou, Weiyou; Tian, Peng; Sun, Fu'an; He, Mingyang; Chen, Zaixin
Abstract On the basis of the mechanism of Baeyer–Villiger (B‐V) oxidation, a bifunctional catalyst based on tetra(4‐sulfonato‐phenyl)porphinato‐cobalt(II) anion (CoTSPP) intercalated into Zn2Al hydrotalcite (Zn2Al‐LDH; LDH=layered double hydroxide) was designed and prepared. XRD, FTIR, DR UV/vis, TG/DTA, and SEM characterization indicate that CoTSPP molecular has been successfully intercalated into the layers of Zn2Al‐LDH. The catalytic activity of the synthesized hybrid in the B‐V oxidation for various ketones is excellent. Control experiments indicated that the catalyst has a bifunctional role in the reactions. The protocol opens up new perspectives in the rational design of efficient catalytic systems.